2023
DOI: 10.1097/bot.0000000000002568
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Increased Time to Surgery in Geriatric Patients With Acetabular Fractures

Abstract: Objectives: To explore the association between time to surgery (TTS) and postoperative complications in geriatric patients with acetabular fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Thus, establishing recommendations is only possible with reservations. Seilern and Aspang et al examined the correlation between the timing of surgery after trauma and the occurrence of postoperative complications in geriatric patients [38]. In their study, 51 patients were retrospectively analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, establishing recommendations is only possible with reservations. Seilern and Aspang et al examined the correlation between the timing of surgery after trauma and the occurrence of postoperative complications in geriatric patients [38]. In their study, 51 patients were retrospectively analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…They found that geriatric patients who underwent an operation after more than 48 h had a 5-fold increased risk of developing postoperative major complications, such as myocardial infarction, pulmonary artery embolisms (LAEs), deep venous thrombosis, ARDS, or renal failure, as well as less serious complications, such as pneumonia, delirium, urinary tract infections, or superficial wound infections, as compared to the group that underwent an operation within 48 hours. In addition, early-operated patients had a 7-day shorter hospital stay [38]. A review from Mansour et al found that operative stabilization within 48 h improves repositioning quality and correlates with a statistically nonsignificant shorter surgery time.…”
Section: Discussionmentioning
confidence: 99%